An evaluation of the teaching readiness of intermediate science teachers in the division of Angeles City - Garma, George R. 1935- ([Quezon City s.n.], 1973)
The teaching readiness of the public intermediate school science teacher in the Division of Angeles City was determined in this paper. Specifically, this research work sought to examine the readiness of the teachers as shown by their academic transcripts of records and Civil Service Form 212, and on the basis of their performance in the battery tests covering areas such as process and content of science, teaching approach, and construction of instructional objectives and evaluation items.
Thesis (Master of Arts in Teaching Elementary Science)--University of the Philippines Diliman.
Keywords: Teaching, Rating of; Science -- Study and teaching (Elementary).